Transferability of PCR-based diagnostic protocols: An international collaborative case study assessing protocols targeting the quarantine pine pathogen Fusarium circinatum - Nowakowska, Justyna Anna; Ioos, Renaud; Mullett, Martin; Vettraino, Anna Maria; Douanla-Meli, Clovis; Cornejo, Carolina; Alves, Artur; Diez, Julio J.; Ahumada, Rodrigo; Kanetis, Loukas; Berbegal, Mónica; Luchi, Nicola; et al. (My University, 2019)
Fusarium circinatum is a harmful pathogenic fungus mostly attacking Pinus species and also Pseudotsuga menziesii, causing cankers in trees of all ages, damping-off in seedlings, and mortality in cuttings and mother plants for clonal production. This fungus is listed as a quarantine pest in several parts of the world and the trade of potentially contaminated pine material such as cuttings, seedlings or seeds is restricted in order to prevent its spread to disease-free areas. Inspection of plant material often relies on DNA testing and several conventional or real-time PCR based tests targeting F. circinatum are available in the literature. In this work, an international collaborative study joined 23 partners to assess the transferability and the performance of nine molecular protocols, using a wide panel of DNA from 71 representative strains of F. circinatum and related Fusarium species. Diagnostic sensitivity, specificity and accuracy of the nine protocols all reached values >80%, and the diagnostic specificity was the only parameter differing significantly between protocols. The rates of false positives and of false negatives were computed and only the false positive rates differed significantly, ranging from 3.0% to 17.3%. The difference between protocols for some of the performance values were mainly due to cross-reactions with DNA from non-target species, which were either not tested or documented in the original articles. Considering that participating laboratories were free to use their own reagents and equipment, this study demonstrated that the diagnostic protocols for F. circinatum were not easily transferable to end-users. More generally, our results suggest that the use of protocols using conventional or real-time PCR outside their initial development and validation conditions should require careful characterization of the performance data prior to use under modified conditions (i.e. reagents and equipment). Suggestions to improve the transfer are proposed.
Keywords: Gibberella circinata; Pinus radiata; Pitch canker